Rapid increase of gonorrhoea cases in Guangdong Province, China, 2014–2017: a review of surveillance data - Lei Chen; Weiming Tang; Bin Yang; Cheng Wang; Joseph Tucker; Peizhen Zhao; M Kumi Smith; Ngai Sze Wong; Willa Dong; Heping Zheng (BMJ Open)
Objectives An increased trend in the number of reported gonorrhoea cases has been observed between 2014 and 2017 in China. This study aims to describe the reported epidemic of gonorrhoea and potential driving forces in Guangdong Province, China.Design A review of surveillance data.Participants Three different sources of data from Guangdong Province were analysed: gonorrhoea cases reported to the Chinese sexually transmitted infections (STI) case report system (CRS); a clinic-based retrospective study conducted to collect information on annual gonorrhoea screening coverage and data from the Guangdong governmental sentinel surveillance network (SSN) to examine the gonorrhoea prevalence among males attending STI clinics.Outcome measures Reported incidence of gonorrhoea, number of reported gonorrhoea cases, number of screening tests for gonorrhoea and gonorrhoea prevalence.Results The STI CRS data showed that the reported incidence of gonorrhoea has increased rapidly from 15.7 cases per 100 000 population in 2014 to 27.3 cases per 100 000 in 2017 in Guangdong (p<0.001). Regions with a reported incidence of gonorrhoea cases of more than 10 cases per 100 000 expanded from 7 cities in 2014 to 13 cities in 2017. The SSN data showed that the gonorrhoea prevalence among males attending STI clinics increased from 2.7% in 2015 to 3.6% in 2017 (p=0.14). The retrospective study showed that the increased rate of screening for gonorrhoea between 2014 and 2017 was 35.0%, which was much lower than the increased rate of the number of reported gonorrhoea cases (123.3%).Conclusions The number of gonococcal infections is rapidly rising in Guangdong, China. Expanded screening coverage, use of more sensitive diagnostics and increase of gonorrhoea prevalence are three potential contributors to the epidemic. Additional targeted intervention strategies are necessary in the future to control the epidemic.